Effects of Tea Consumption on Anthropometric Parameters, Metabolic Indexes and Hormone Levels of Women with Polycystic Ovarian Syndrome: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Shen, Wenjuan; Pan, Yujia; Jin, Bao; Zhang, Zongyu; You, Tianjiao; Qu, Yangfan; Han, Mei; Yuan, Xingxing; Zhang, Yang (Frontiers in Endocrinology, 2021)
Objective Our aim was to conduct a systematic review and meta-analysis to assess the effectiveness and safety of tea supplements for patients with polycystic ovary syndrome (PCOS). Methods We conducted searches of the published literature in PubMed, EMBASE, Cochrane Library, Web of Science, Chinese Biomedical Literature Database, Chinese National Knowledge Infrastructure (CNKI), VIP database, and Wanfang Database in 1985 to September 2021. Data from randomized controlled trials (RCTs) were obtained to assess the effects of tea versus placebo in women with PCOS. Weighted mean differences (WMDs) were pooled using a random-effects model or risks ratios (RRs) using a random-effects model. Results Six RCTs (235 participants) were included in our systematic review. Tea supplements as adjuvant therapy led to greater improvement in body weight (WMD −2.71, 95% CI −4.95 to −0.46, P = 0.02, I2 = 0%), fasting blood glucose (FBG: WMD −0.40, 95% CI −0.59 to −0.20, P < 0.0001, I2 = 0%) and fasting insulin (FINS: WMD −3.40, 95% CI −4.76 to −2.03, P < 0.00001, I2 = 0%) when compared with placebo. There were no significant differences of body mass index, waist circumference, hip circumference, waist-to-hip ratio (WHR), body fat rate, total testosterone, free testosterone (FT), dehydroepiandrosterone, luteinizing hormone or follicular-stimulating hormone (FSH) between the two groups. In addition, subgroup analysis suggested that green tea was effective on body weight, FINS, FBG, FT, and FSH, and herbal tea can also reduce FT levels, tea supplements had a significant impact on FBG and FSH in trials with intervention duration ≥ 3 months, and intervention lasting less than 3 months can improve FINS. Tea had significant effect on reducing WHR, FBG and FSH in Asian PCOS patients, but not in Caucasians. And there was no statistically significant effect of tea on weight and FINS in Asians, but it was effective for Caucasian participants. Compared with placebo, tea supplements did not cause significant adverse reactions (RR 1.45, 95% CI 0.30 to 6.90, P = 0.65, I2 = 0%). Conclusion This meta-analysis suggests that consumption of tea supplementation in women with PCOS could significantly decrease the levels of FBG and FINS as well as reduce body weight. Especially green tea, not only has the above effects, but also has a significant effect on improving a variety of reproductive hormone indexes. Furthermore, tea supplementation is a relatively safe therapy for PCOS patients. Systematic Review Registration PROSPERO https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=212755, identifier CRD42021249196.